Genotoxic properties of materials used for endoprostheses: Experimental and human data. (November 2020) - Qin, Hong-Min; Herrera, Denise; Liu, Dian-Feng; Chen, Chao-Qian; Nersesyan, Armen; Mišík, Miroslav; Knasmueller, Siegfried
Abstract: Approximately 2 million endoprostheses are implanted annually and metal ions as well as particles are released into the body from the materials which are used. This review describes the results of studies concerning genotoxic damage caused by artificial joints. DNA damage leads to various adverse long-term health effects in humans including cancer. Experiments with mammalian cells showed that metal ions and particles from orthopedic materials cause DNA damage. Induction of chromosomal aberrations (CA) was found in several in vitro experiments and in studies with rodents with metals from orthopedic materials. Human studies focused mainly on induction of CA (7 studies). Only few investigations (4) concerned sister chromatid exchanges, oxidative DNA damage (2) and micronucleus formation (1). CA are a reliable biomarker for increased cancer risks in humans) and were increased in all studies in patients with artificial joints. No firm conclusion can be drawn at present if the effects in humans are due to oxidative stress and if dissolved metal ions or release particles play a role. Our findings indicate that patients with artificial joints may have increased cancer risks due to damage of the genetic material. Future studies should be performed to identify safe materials and to study the molecular mechanisms in detail. Highlights: Approximately 2 million endoprostheses are implanted annually. Metal ions and particles are released into the body from the materials which are used. Patients with artificial joints may have increased cancer risks.